2006
DOI: 10.1051/0004-6361:20066582
|View full text |Cite
|
Sign up to set email alerts
|

Co-orbital terrestrial planets in exoplanetary systems: a formation scenario

Abstract: Aims. We study the formation of a hypothetical terrestrial-type body in the equilateral Lagrange points of a giant extrasolar planet. Starting from a swarm of planetesimals in stable tadpole orbits, we simulate its dynamical and collisional evolution under a wide range of different initial conditions and masses for both the Trojan population and its planetary companion. We also analyze the effects of gas drag from the interaction of the planetesimals with the nebular disk. Methods. The formation process is sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 32 publications
(42 reference statements)
0
73
0
Order By: Relevance
“…For the high mass ratio border the B 1:1 resonance limits the librational motion originating from the point (µ c , 0) (Danby 1964;Érdi et al 2007). A number of type A resonances appear in the low mass region, while the B 2:1 resonance (see Figure 3) is responsible for the large gap.…”
Section: Lyapunov Indicatormentioning
confidence: 95%
See 1 more Smart Citation
“…For the high mass ratio border the B 1:1 resonance limits the librational motion originating from the point (µ c , 0) (Danby 1964;Érdi et al 2007). A number of type A resonances appear in the low mass region, while the B 2:1 resonance (see Figure 3) is responsible for the large gap.…”
Section: Lyapunov Indicatormentioning
confidence: 95%
“…Besides the planetary (P-type) and satellite (S-type) motion around both respectively one of the components, T-type motion was considered as a third possibility. Not only the formation of Earth-mass planets directly in T-type orbits (about a migrating gas giant in a proto-planetary disk) was studied (Beaugé et al 2007), but also the possible capture of asteroids into Trojan orbits by the inner planets (Schwarz & Dvorak 2012 Funk et al (2012). Since extrasolar planets were also detected in binary star systems and systems consisting of a star and a sub-stellar companion, the dynamics of librational motion at high mass ratios is of interest, especially for the non-coplanar motion.…”
Section: Extrasolar Systemsmentioning
confidence: 99%
“…This makes the existence of one or two (in L4 and L5) Io-mass satellites possible. Beaugé et al (2007) also studied the type II migration of a giant planet assuming that its semimajor axis decayed on a time scale of 10 5 − 10 7 years. Their results showed that the Trojan satellite migrated together with the planet, and that the tadpole configuration close to L4 was maintained.…”
Section: Possible Origin Of Trojan Satellitesmentioning
confidence: 99%
“…More recently, Goździewski and Konacki (2006) showed that two planets in stable co-orbital motion and non-coplanar orbits could yield similar radial velocity curves, albeit with significantly larger residuals. However, the existence of co-orbital giant planets is far from being established, and there is evidence that planetary bodies with masses larger than ∼ 0.7M ⊕ could not be accreted in the equilateral Lagrange points of giant exoplanets (Beaugé et al 2007). Even so, it is very curious how co-orbital bodies can mimic the radial velocity curve of two bodies in a 2/1 MMR.…”
Section: Orbital Determination Of Resonant Planetsmentioning
confidence: 99%